"Fuller" or "extended" working lives: a critical commentary. (2nd December 2014) - Phillipson, Chris
Abstract : Purpose: – The purpose of this paper is to, first, provide some background to the treatment of older workers; second, highlight the distinction between a "fuller" and an "extended" working life; third, note the importance of separating out different groups within the category "older worker"; finally, identify areas for action to suppose those now facing working into their 60s and beyond. Design/methodology/approach: – Commentary paper analysing development of policies towards older workers. Findings: – This paper identifies problems implementing policy of extending working and provides various areas of action to support older workers. Research limitations/implications: – This paper suggests extending work unlikely to be achieved without ensuring greater security for older workers. Practical implications: – Importance of developing more support for older workers. Social implications: – Challenge of resolving insecurity in the labour force as an impediment to extended working. Originality/value: – This paper outlines a critical assessment of current government policy towards older workers.